Implementasi Aplikasi Canva dalam Mendukung Pembelajaran di SDN 75 Kota Bengkulu - Nurhikma; Triyan Triyan; Nurhayat Lestari Putri; Padhilah Padhilah (jurnal ABDIMAS Indonesia, 2025)
This study aims to describe the implementation of the Canva application in supporting the learning process at SDN 75 Kota Bengkulu. Canva is a digital graphic design application that offers ease in creating engaging and interactive learning media. The research employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The subjects of the study included classroom teachers, students, and the school principal. The results showed that the use of Canva had a positive impact on enhancing teachers' creativity in designing teaching materials and increasing students' learning interest. Teachers were able to create more communicative and comprehensible visual materials, while students demonstrated higher enthusiasm during the learning process. Challenges encountered included limited technological facilities and initial unfamiliarity with the application, which were addressed through ongoing training and assistance. Thus, the implementation of Canva at SDN 75 Kota Bengkulu has proven effective in supporting more engaging, interactive, and contextual learning in the digital era.